Kānsammanā "thitthāng Prathēt Thai nai miti watthanatham phāitai phǣn prō̜ngdō̜ng hǣng chāt" (Samnakngān Palat, Krasūang Watthanatham, 2010)
Report of a seminar on direction of the Ministry of Culture under the national reconciliation plan and poltical situation in Thailand.